The contribution of the traditional game of congklak to mathematics learning: How is the relationship and influence of interest, cooperative character and student responses - Kamid Kamid; Sofnidar Sofnidar; Sabila Eka Septi; Yulita Dwi Citra (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
This study tested a sample of 70 students with variables of interest, cooperation skills and responses in the math game of congklak from two schools, namely SD IT Aulia and SDN 112/I Perumnas. The objectives of the study: (1) to determine the comparison between interest, cooperative character and student responses in the traditional game of congklak in mathematics. (2) to determine the relationship of interest, cooperation with students' responses to the traditional game of congklak in mathematics. This type of research uses quantitative methods with a comparative type. The instrument in this study used a questionnaire on interests and observation sheets, namely the character of cooperation and student responses to the traditional game of congklak in mathematics. The results of the T-test obtained based on the table can be found that there is a relationship between interest, cooperative character and student responses in the traditional game of Congklak. In the table-based test, it can be said that there is a relationship between interest, cooperative character and student responses to the traditional game of congklak in mathematics